Cervical cancer and self-responsibility: modeling the risk of refraining to undergo a papanicolaou test among Chilean women by decision trees - Carlos Rodríguez Garcés (Horizonte Médico, 2018)
Objective: To model by statistical means the risk levels of refraining to undergo a papanicolaou test among Chilean women according to sociodemographic variables. Materials and methods: National Socioeconomic Characterization Survey (CASEN). Sample of 73,324 cases, according to CASEN’s data. Modeling by decision trees to establish the profile of women who refrain from undergoing a papanicolaou test, and then analyze the reasons for that decision. Results: The risk of refraining to undergo a papanicolaou test varies considerably and depends on variables such as other cancer preventive tests (not undergoing a mammography), adulthood stage (late phase), and marital status. The traditional lack of information and access is replaced by personal reasons as the frequent excuse for not undergoing a papanicolaou test on a continuous basis. Perception of unusefulness and lack of time cause this refraining behavior as a decision and not as an impossibility. Conclusions: The results question contemporary women’s characteristics and behaviors, and pose the need for considering a social-educational intervention as a requirement to generate favorable attitudes towards prevention. These factors should be considered by social policy on cancer prevention in general, and particularly in cervical cancer prevention